An Analysis Cinta Laura Language Style in the Podcast - Andina Yunianti; Rosita Ambarwati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
Language style is a person's style in conveying information or the intent of the thing to be conveyed. Everyone has a different style of language when conveying something. The purpose of this study is to show the use of language styles from conversations in one of the podcasts. This article analyzes the use of language style in conversation, there are differences in the style of language used by the sources. This article displays an understanding of the style of language from several styles of language and displays some of the use of language styles in conversations used by the speakers. Furthermore, this article explains the differences in the use of styles the language of some of these styles include frozen style, formal style, consultative style, relaxed style, familiar style. There are several things that can cause stylistic grouping. These factors include participants, topic of conversation, place and its functions. One important key is that every language always has fixed characteristics at all times. Technically, in terms of communication, modifications to the use of language such as the style of language one uses when speaking according to the situation and the other person. The results of this study are that the use of a consultative and casual style is more dominant than other language styles when the resource persons speak in this podcast.